The Validity of Ijab Kabul Pronunciation in the View of Aceh Singkil Scholars: Keabsahan Pengucapan Ijab Kabul Menurut Pandangan Ulama Aceh Singkil - Nasrun, Mahdalena; Shalawati, Shalawati (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2021)
The pronunciation of Ijab Kabul is a phenomenon that the Aceh Singkil Ulama respond to in contradiction, so that it becomes an interesting material to be discussed according to the Aceh Singkil Ulama. The research question in this thesis is, How is the legal consent in marriage according to the views of the Aceh Singkil Ulama. And what is the legal basis used by the Aceh Singkil Ulama against the conditions for the validity of the consent and acceptance in the marriage contract. In the discussion of this thesis using (Field research). The data sources are primary data sources and secondary data sources. Based on the research results obtained show that; First, the pronunciation of Ijab Kabul is something that is easy to pronounce, not to be complicated for men and the Aceh Singkil Ulama make it easier to pronounce the Ijab Kabul for those who carry out this marriage, namely being able to use their own language (regional language), the most important thing is not to deviate from the meaning of marriage. (al-zawaj). Second, the legal basis regarding the pronunciation of consent and consent in Surah Az-Zariyat verse 49